Más allá del positivismo: una interpretación lakatosiana de la enseñanza de las ciencias - Níaz, M. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
The history of science shows that positivism was the dominant philosophy from about the end of the 19th century to the middle of the 20th century. The main objective of this article is to present a critique of positivist ideas and show how the new philosophy of science, as represented by Lakatos, has important implications for science education.